ULTRASONOGRAPHIC AND HISOPATHOLOGICAL CHANGES IN DOGS WITH CHRONIC RENAL DISEASE - S. Kavitha; A.P.Nambi; S.R. Srinivasan; C.Balachandran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
One hundred and two geriatric dogs presented with chronic renal disease were further examined for ultrasonographic and histopathological alterations. Hyperechoic cortex, indistinct corticomedullary junction and  altered renal architecture were observed in 80 per cent dogs. The remaining 20 per cent dogs had no significant changes. The histopathological lesions detected in 12 dogs subjected to post mortem examination were interstitial fibrosis, moderate to severe plasma cell infiltration of interstitium, calcification of tubules, loss of tubular epithelial cells, atrophy of glomeruli and thickening of basement membrane.